MUSIC THERAPY FOR PAIN AND ANXIETY IN HOSPITALIZED CHILDREN: A SYSTEMATIC REVIEW OF RANDOMIZED CONTROLLED TRIAL - Arvida Bar; Monalisa; Netha Damayantie; Halimah (OPI Napoli, 2023)
Introduction. Music has been widely recognized for its effectiveness in controlling anxiety and pain. However, in particular groups such as children, the implementation may be challenging, especially regarding the type of music selection. The aim of the study is to evaluate the music therapy efficacy on pain and anxiety management in pediatric care to improve the management of pain and anxiety in the pediatric population. Methods. This review was written according to the Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA) statement. In assessing the impact of music therapy as a method of pain and anxiety management in pediatric care, a database tracking was conducted for articles publicized between 2000 and 2022. The databases used including Sciencedirect, Cochrane library, PubMed, and Wiley online library. Articles were deemed if the study subjects ranged in age from 0 to 21 years old, the intervention was live or recorded music, and the study took place in an inpatient background. Results. 1,129 publications were discovered. In final search of literature, there are 12 articles included in this review. There is consistent and consequential evidence that music may relieve pain and anxiety in hospitalized children before and during procedures. The type of music that is widely used is classical and traditional instrumental music. In addition, there were only two studies using nursery rhymes. Conclusion. The patient's preference in choosing music for children enables them to determine the appropriateness of therapy. Classical music can be the main choice in applying music therapy in reducing anxiety and pain in children.